Social Psychology in Forensic Practice - Harvey, Joel; Ambrose, Derval (New York: Routledge, 2023)
"This book explores how different social psychology theories and concepts can be applied to practice. Considering theories from attribution theory to coercion theory, social identity theories to ostracism, the authors offer a greater understanding and appreciation of the ways in which social psychology can contribute to forensic practice. This book will interest graduate and undergraduate students and researchers in criminology, sociology, and forensic, social and clinical psychology. It will also be of practical use to health professionals and non-health professionals working in forensic settings as well as policy makers and others commissioning forensic services"--
Includes bibliographical references and index.
Keywords: Social psychology; Forensic psychology